The impact of home care based on the Continuous Care Model by family caregivers on activities of daily living of stroke patients - Pourshirvani, Azita; Abed Saieedi, Jila; Nekozad, Niloofar; Zandi, Mitra (Advances in Nursing & Midwifery, 2017)
Abstract Background and Aim: Interventions to support stroke care givers by providing education and Training in skills essential for the day to day management of disabled stroke survivors have shown a little impact in reducing the burden of care but there are many recommended to use a more effective skill. We evaluated the effectiveness of caregiver training by Continuous Care Model to increasing patient’s functional squeal and improving patient and caregiver outcomes. Materials and Methods: This research was a quazi-experimental study. A total number of 90 cases were equally divided into two groups. Continuous Care Model training was applied to the caregiver in the experimental group until ten weeks after discharge. In the same time, the control group was treated based on routine protocol. Main outcome was measured for patients, by Functional Independence Measure, which measures patient’s functional status. Recovery was quantified by the changes in the Functional Independence Measure total scores. Caregiver demographic and care home checklist for Caregiver, was completed by the researcher too. Finding: Although Wilcoxon test showed significant differences in the mean scores of Functional Independence Measure (p<0/001) in each group, We used the Mann-Whitney test to compare differences in mean of changes Functional Independence Measure between two groups after intervention and it showed changes in experimental group (P<0/001) was more than control group. Conclusion: Training care givers by Continuous Care Model can improve functional recovery, and activities of daily living of stroke patients. Keywords: Home care; Caregivers, Activities of Daily Living; Stroke; Patients